New horizons of theatre: Digital practices and their significance for contemporary theatre arts - Lyudmila P. Maryina; Elizaveta S. Kochergina (Управление культурой)
Digitalization is changing the contemporary theatre, posing new challenges. The article examines how technologies – from virtual reality to online platforms – are transforming the perception of viewers, creating new performance formats and changing promotion strategies. Particular attention is paid to the role of the viewer, who from a passive observer becomes an active participant, as well as the influence of social networks on the formation of a loyal audience. The transformation of traditional forms, viewer experience and theatrical space under the influence of virtual and augmented reality, interactive media and online formats is noted. Both the positive aspects of digitalization – the creation of new theatre formats, increasing the availability of theatrical art for a remote audience – and the risks associated with it are described – the possible displacement of live theatre and the strengthening of digital inequality, which can lead to a “digital divide” between those who have the skills to use technology and those who do not. Digital theatre plays an important role in the modern cultural environment, adapting to audience demands and experimenting with new formats. He successfully integrates traditional methods with innovative digital approaches, creating multimedia performances that expand the boundaries of theatrical art and open up new opportunities for interaction with the audience. The aim of the study was to examine the impact of digitalization on contemporary theatrical art. The article uses analytical, comparative, historical and comparative research methods, as well as expert interviews, an online survey of the target audience to study new trends in digital theater, emphasizing their impact on the interaction of viewers with art. The theoretical basis of the study is formed by concepts dedicated to the impact of digitalization on contemporary theater. The work analyzes how digital technologies, such as online broadcasts and new formats, transform theatrical art, the audience experience and the interaction between the theater and the audience. At the same time, it is emphasized that digital tools do not replace live theater, but expand its capabilities, helping to attract a new audience. The empirical basis of the study is the Federal State Budgetary Institution of Culture "Russian State Academic Bolshoi Drama Theater named after G. A. Tovstonogov", as an example of an institution that was one of the first in Russia to try out digital theater, and the Theatre HD project, which is a unique digital theater format based on high-quality broadcasts of theatrical productions and performances. The possibilities of using digital platforms to expand the audience and engage viewers, including the implementation of online projects and interactive formats, are described using the experience of the BDT named after G. A. Tovstonogov as an example of the adaptation of the theater to the virtual environment.